2011
DOI: 10.1016/j.ajog.2010.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus prophylaxis in patients who report a penicillin allergy: a follow-up study

Abstract: Conclusion-With directed intervention, adherence to the 2002 CDC guidelines for GBS prophylaxis in penicillin-allergic women improved dramatically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
1
16
0
1
Order By: Relevance
“…This is especially true with positive GBS bacteriuria results (58.2% of women with vaginal GBS colonization had testing performed compared with 28.0% of women with GBS bacteriuria). These findings are similar to those found by Critchfield et al 12 Strengths of this study include that it was performed at a large institution and is one of few studies that has looked specifically at GBS prophylaxis in women with a penicillin allergy without reported anaphylaxis.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is especially true with positive GBS bacteriuria results (58.2% of women with vaginal GBS colonization had testing performed compared with 28.0% of women with GBS bacteriuria). These findings are similar to those found by Critchfield et al 12 Strengths of this study include that it was performed at a large institution and is one of few studies that has looked specifically at GBS prophylaxis in women with a penicillin allergy without reported anaphylaxis.…”
Section: Discussionsupporting
confidence: 89%
“…20,21 A 2011 retrospective study performed at the same institution found that, after the implementation of interventions to improve adherence to the CDC guidelines, the proportion of GBS-colonized, penicillin-allergic women receiving appropriate antibiotics increased from 16.2% in 2004-2006 to 76% in 2008. 12 Our study found many fewer women received appropriate intrapartum antibiotic prophylaxis over a similar timeframe. This study by Critchfield et al, 12 however, looked at all women with a reported penicillin allergy and did not categorize women into high and low risk for anaphylaxis to penicillin.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Igazolódott, hogy az újszülöttek fertőzése úgy előzhető meg, ha a baktériumot hordozó terhes a szülés megindulása után legalább két alkalommal, négy óra különbséggel, intravénás penicillin-vagy ampicillinkezelésben részesül [2,3]. Alternatív antibiotikum adá-sára csak a penicillinallergiás terhesek szorulnak [4].…”
Section: Prevention Of Neonatal Group B Streptococcal Sepsis In Hungaunclassified